Conservation of time-based media art - Engel, Deena; Phillips, Joanna (Routledge, Taylor & Francis Group, 2023)
Caring for time-based media art -- Building a workplace -- Cross-medium practices in time-based media conservation -- Medium-specific practices in time-based media conservation.